The effect of α-melanocyte stimulating hormone on burn-induced oxidant production by rat peritoneal neutrophils - (:unkn) unknown (My University, 2003)
Objective: Previous findings related to the antiinflammatory effects of α-melanocyte stimulating hormone (α-MSH) indicate that the peptide might inhibit inflammation by antagonizing the effects of local cytokines or by inhibiting neutrophil functions. In addition, it is a potent inhibitor of the induction of the inducible nitric oxide synthase (iNOS) in cultured macrophages and of nitric oxide (NO) production in a sepsis model. This study was designed to investigate whether α-MSH affects reactive oxygen metabolite production by rat peritoneal neutrophils following burn injury and whether NO is involved in this effect. Methods: The neutrophils were removed from the peritoneum of the rats 6 h after burn or sham trauma. Cells (2 × 10 6 /ml) were treated with the increasing concentrations of α-MSH (10-12 M, 10-10 M, 10-8 M or 10-6 M). Nitric oxide donor, sodium nitroprusside ranging from (10-10 - 10-4 M) was added to the cells in the presence of α-MSH. Reactive oxygen metabolite production was measured by chemiluminescence (CL) technique using luminol or lucigenin probes. Results: Lucigenin CL value of cells obtained from burn animals was significantly higher than those obtained from the sham group. α-MSH caused significant reductions in high lucigenin CL values and this effect was partly inhibited by sodium nitroprusside. Conclusion: Our results suggest that α-MSH is effective in preventing oxidant production by neutrophils activated by burn trauma, at least in part, by a mechanism involving nitric oxide.
Keywords: α-melanocyte-stimulating hormone; Burn; Chemiluminescence; Nitric oxide; Reactive oxygen species